Synthesis and Evaluation of New Pyrazoline Derivatives as Potential Anti-breast cancer Agents - Mariam Abubaker Salem (African Journal of Advanced Pure and Applied Sciences, 2026)
Using creative, effective anticancer therapeutics, new kinds of heteroaryl pyrazoline compounds were synthesized, designed, and studied based on their anti-proliferative effects against breast cancer cell lines. The following pyrazoline derivatives were designed and synthesized: 5-(naphthalene-2-yl)-3-(phenyl)-1-tosyl-1H-pyrazole (NAPT) and 3-(4-N,N-dimethylamino)-phenyl)-5-(naphthalene-2-yl)-1-tosyl-1H-pyrazole (DMNAPT) Using naphthyl-chalcone derivatives, pyrazoline derivatives were synthesized and were determined using IR and ¹H-NMR spectra. Antitumor activity was also evaluated using the MTT assay. It was discovered that the compounds synthesized from 2-naphthyl chalcones (M1 and M2) exhibited relatively better anti-proliferative activity against MCF-7 breast cancer cells. Among the compounds that were evaluated, NAPT and DMNAPT were observed to have significantly moderate anti-proliferative activity on the MCF-7.